Cloning and characterization of the Salmonella typhimurium ada gene, which encodes O6-methylguanine-DNA methyltransferase. - Hakura, A (1991)
The ada gene of Escherichia coli encodes O6-methylguanine-DNA methyltransferase, which serves as a positive regulator of the adaptive response to alkylating agents and as a DNA repair enzyme. The gene which can make an ada-deficient strain of E. coli resistant to the cell-killing and mutagenic effects of N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) has been cloned from Salmonella typhimurium TA1538. DNA sequence analysis indicated that the gene potentially encoded a protein with a calculated molecular weight of 39,217. Since the nucleotide sequence of the cloned gene shows 70% similarity to the ada gene of E. coli and there is an ada box-like sequence (5'-GAATTAAAACGCA-3') in the promoter region, we tentatively refer to this cloned DNA as the adaST gene. The gene encodes Cys-68 and Cys-320, which are potential acceptor sites for the methyl group from the damaged DNA. The multicopy plasmid carrying the adaST gene significantly reduced the frequency of mutation induced by MNNG both in E. coli and in S. typhimurium. The AdaST protein encoded by the plasmid increased expression of the ada'-lacZ chromosome fusion about 5-fold when an E. coli strain carrying both the fusion operon and the plasmid was exposed to a low concentration of MNNG, whereas the E. coli Ada protein encoded by a low-copy-number plasmid increased it about 40-fold under the same conditions. The low ability of AdaST to function as a positive regulator could account for the apparent lack of an adaptive response to alkylation damage in S. typhimurium.